Implementation of Tatanén di Balé Atikan in Fostering Islamic Morality among Elementary School Students - Maspiah, Imas Maspiah; Setiawan, Usep; Wulandari, Dyah; Ridwanulloh, Muhammad Syabani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This research aims to examine how the planning, organization, implementation, and monitoring of the Tatanén di Balé Atikan program were carried out in elementary schools to foster students’ Islamic character. This research used a qualitative approach using a phenomenological research method. Data were collected through interviews, observations, and documentation. The research findings indicated that the implementation of the Tatanén di Balé Atikan (TdBA) program at SDN Ciwangi instilled Islamic moral values in students through concrete habituation practices, including self-discipline, cooperation, care for nature, obedience in worship, and love for the homeland. This program was systematically planned by involving the three centers of education, namely school, family, and community, organized through working groups and activity schedules, and implemented in an integrated manner within intracurricular, co-curricular, and extracurricular programs and activities using a Sundanese local wisdom approach. Although internal supervision functioned well, external supervision had not yet been implemented optimally, indicating the need for stronger, continuous monitoring to ensure that the benefits of TdBA are more effectively shaped to students’ Islamic character